Ozone applied to the homogeneous charge compression ignition engine to control alcohol fuels combustion. (15th December 2015) - Masurier, J.-B.; Foucher, F.; Dayma, G.; Dagaut, P.
Highlights: Ozone was useful to control combustion phasing of alcohol fuels in HCCI engine. Ozone helps to improve the combustion and advance its phasing. Butanol is more impacted by ozone than methanol and ethanol. HCCI combustion parameters may be controlled by managing ozone concentration. Kinetics demonstrates that alcohol fuels are initially oxidized by O-atoms. Abstract: The present investigation examines the impact of seeding the intake of an HCCI engine with ozone, one of the most oxidizing chemical species, on the combustion of three alcohol fuels: methanol, ethanol and n-butanol. The research was performed through engine experiments and constant volume computations. The results showed that increasing the ozone concentration led to an improvement in combustion coupled with a combustion advance. It was also observed, by comparing the results for each fuel selected, that n-butanol is the most impacted by ozone seeding and methanol the least. Further analyses of the experimental results showed that the alcohol fuel combustion can be controlled with ozone, which presents an interesting potential. Finally, computation results confirmed the experimental results observed. They also showed that in presence of ozone, alcohol fuels are not initially oxidized by molecular oxygen but by O-atoms coming from the ozone decomposition.